The long gamma nail: a DGH experience. - Edwards, SA; Pandit, H; Clarke, H (2000)
Subtrochanteric fractures constitute a difficult problem for the trauma surgeon. The long Gamma nail (LGN) represents an efficient technique in the management of these fractures. A retrospective analysis of 51 LGN with an average follow up of 16 weeks is presented. The average age of the patients was 72 years and the mean time to union was 11 weeks. The incidence of peroperative, early local and late local complications was 8, 8 and 4%, respectively or 20% in total. The thirty-day mortality was 8%. Our results in the use of the LGN have been good. Its introduction provides the trauma surgeon with a tool for allowing earlier mobilisation, decreasing operative time, surgical trauma, blood loss and wound problems. The LGN is a device by which most complex fractures in the proximal femur can be managed with a single implant.